PENINGKATAN PENDAPATAN MASYARAKAT PEDESAAN DALAM HUBUNGANNYA DENGAN DISTRIBUSI ANTAR RUMAH TANGGA - NURMANAF, A. ROZANY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
The purpose of this study is to show interrelation between the level of development successful and income distribution inequality among households. By using Patanas data 1999 especially the information that covered household income aspect, this study identify the shape of relationship between two parameters these are the skewness of household income distribution that is measured by Gini Index value and level of income that is calculated in income per head. Based on the village analysis unit, the discussion focused on the shape of the two in order to examine Kuznets hypothesis that represent by U-shape pattern. The analysis of study verified that the relationship support the hypothesis. It means, increasing in household income followed by increasing in household income distribution skewness especially in the beginning of development phase; but this tendency change in opposite way in next development phase. While, the level of income distribution skewness have positive correlation with three income factors, these are distribution of agricultural income, distribution of household member education level and distribution of agricultural land holding. Besides, the distribution of agricultural income is affected by the distribution of agricultural land holding, especially in the area where agricultural sector has a higher contribution on the economy of society.
Keywords: Income Level, Income Distribution, Gini Index